The Effect of Summarization Strategy on Reading Comprehension through Summary Writing Ability - Shibabaw, Aragaw; Alemu, Marew; Tesfa, Agegnehu (Ethiopian Renaissance Journal of Social Sciences and Humanities, 2023)
This study was conducted to investigate the role of summarizing ability as mediator of the effect of summarization strategy on reading comprehension. The study employed a quasi-experimental pre-test and post-test control group design. It was carried out at Azezo Tseda kifleketema Atse Fasil Elementary School. Intact classes of 7th1 (n=54) and 7th2 (n=55) students participated as experimental and control groups, respectively. Students in the treatment and controle groups completed eight reading comprehension lessons using the summarization strategy and the conventional strategy respectively. From them, pre- and post-intervention data were obtained through tests. The data were analyzed through covariate-based structural equation modeling (CB-SEM) using SPSS AMOS v.20. Pretest datawere covariated and controlled. The statistical model showed that summarization strategy has a significant positive direct effect (β = 2.410, CR = 3.948, p< .005) on summarizing ability; on the other hand, summarizing ability has no significant direct effect (β =.178, CR = 1.460, p =.108) on reading comprehension. The strategy also has no significant indirect effect on reading comprehension through summarizing ability (β =.430, p =.109). Therefore, summarizing ability has no mediation role in the relationship between summarization strategy and reading comprehension. Based on the findings, pedagogical and research implications and suggestions were discussed and indicated.